Infectious risk of elderly patients on peritoneal dialysis: Experience of a portuguese center - Belino, C. (2018)
Background: The goal of this study was to compare the risk of peritoneal dialysis‑related infections in younger and older patients and to identify risk factors for infection in elderly patients. Methods: We performed a longitudinal retrospective study on a population of Portuguese peritoneal dialysis patients treated at the same center between January 2005 and December 2015. Clinical and laboratory data were collected from medical reports. Two groups of patients were compared: non elderly (< 65 years) and elderly (≥ 65 years). Results: Among 100 patients, there were 73 non elderly (median age 52 years) and 27 elderly (median age 74 years). Elderly patients were not associated with higher PD‑infection rates or with less time to PD‑related infections. Cerebrovascular disease was the only significant adverse predictor of peritonitis in elderly (crude HR 3.8; 95% CI 1.10 to 13.34; P = 0.035) and those with higher levels of serum albumin were less likely to develop peritonitis (crude HR 0.47 per each g/dl of increase; 95% CI 0.24 to 0.89; P = 0.023). Conclusions: In our study, elderly patients did not present a greater risk for peritonitis or catheter‑related infections.